The analytic hierarchy process: an effective multi-criteria decision making tool - Islam, Rafikul (IIUM Press, 2003)
The Analytic Hierarchy Process (AHP) is one of the powerful methods to solve MCDM problems. During the last thirty five years, substantial theoretical works have been done on AHP; simultaneously, the method has been applied to solve a wide range of real-world MCDM problems. Presently, many corporations and government agencies are routinely using the AHP for major policy decisions. In the present book, we are basically concerned with the theoretical works on AHP. In addition to this, using AHP an interesting case-study has been presented.